Hypertrophic cardiomyopathy: comprehensive insights into pathogenic genes and genotype-phenotype associations - Hao, Luwen; Chen, Xin; Qin, Bo (Frontiers in Cell and Developmental Biology, 2026)
Hypertrophic cardiomyopathy (HCM) is a genetically heterogeneous cardiac disorder characterized by unexplained left ventricular hypertrophy and represents a leading cause of morbidity and sudden cardiac death, particularly in young adults and athletes. Early studies focused on morphological features, but advances in molecular genetics have shifted emphasis toward genetic diagnosis, mechanistic insights, and family-based management. Pathogenic variants in sarcomeric genes, especially MYBPC3 and MYH7, are central to disease development, with specific mutation types linked to distinct hypertrophy patterns and clinical outcomes. The phenotype is further modulated by ethnicity, age, and sex, contributing to substantial variability. Implementation of genetic testing has enabled identification of definitive pathogenic variants, highlighting the critical role of genomics in diagnosis and personalized care. Despite progress, challenges remain in interpreting variants of uncertain significance, defining genotype–phenotype correlations, and developing robust risk stratification models and individualized therapeutic strategies. This review summarizes current evidence on the pathogenic gene spectrum, genotype–phenotype correlations, and ethnic- or sex-based variability in HCM, as well as the gene and phenotypic characteristics of pediatric HCM, providing a comprehensive framework for understanding its molecular diversity and guiding precision diagnosis and management.